Peran Kepala Madrasah Sebagai Leader dalam Mengelola Administrasi Pembelajaran - Muhammad Dzikky Firman Syah; Ichwanudin; Aisyah Nuril Ikhwan (Journal Islamic Education, 2024)
This study aims to identify the principal's role as a leader and the madrasah principal's efforts in overcoming challenges at MI Pesantren Anak Sholeh Baitul Qur'an Ponorogo. Using a case study approach with qualitative methods, the research involved in-depth observations and interviews with the principal and teaching staff, as well as analysis of madrasah administrative records to ensure data validity. Analysis was conducted using Miles and Huberman's interactive model, including data reduction, data presentation, and conclusion drawing. The results showed that the madrasah principal has a strategic role in motivating teachers, developing the vision and mission of the madrasah, and managing learning administration innovatively. The transformational leadership approach applied proved effective in creating harmonious collaboration among staff, teachers and students. The findings indicate that the role of the madrasah principal supports mobilizing, guiding, encouraging, coaching and protecting the school community. Despite facing challenges such as limited resources and time management, the madrasah principal managed to overcome these obstacles through collaboration strategies, the use of simple technology and teacher professional development. This research provides important insights into how the role of the madrasah principal as a leader can improve the effectiveness of learning administration in madrasah, as well as a practical reference for other madrasah principals in improving the quality of education in the institution.